Failure analysis of lead‐acid batteries at extreme operating temperatures - Umesh Prasad; Jyoti Prakash; Arunachala Nadar M. Kannan; Venkat Kamavaram; Ganesh K. Arumugam (Battery Energy, 2023)
Abstract The lead‐acid battery system is designed to perform optimally at ambient temperature (25°C) in terms of capacity and cyclability. However, varying climate zones enforce harsher conditions on automotive lead‐acid batteries. Hence, they aged faster and showed lower performance when operated at extremity of the optimum ambient conditions. In this work, a systematic study was conducted to analyze the effect of varying temperatures (−10°C, 0°C, 25°C, and 40°C) on the sealed lead acid. Enersys® Cyclon (2 V, 5 Ah) cells were cycled at C/10 rate using a battery testing system. Environmental aging results in shorter cycle life due to the degradation of electrode and grid materials at higher temperatures (25°C and 40°C), while at lower temperatures (−10°C and 0°C), negligible degradation was observed due to slower kinetics and reduced available capacity. Electrochemical impedance spectroscopy, X‐ray diffraction, and energy‐dispersive X‐ray spectroscopy analysis were used to evaluate the degradation mechanism and chemical and morphological changes.